Mengoptimalkan Model Multiplikasi Kepemimpinan di Era Digital Melalui Pemberdayaan Generasi Muda di Gereja - Boaz Adi Prakoso; Manlian Ronald A. Simanjuntak (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the empowerment of youth leadership in the context of the Christian church in Indonesia, focusing on the challenges faced by youth in leading and contributing to church service amid rapid social, economic, and technological changes. The research method used is a qualitative approach with literature review and in-depth interviews with young people in the church, pastors, and Christian leadership practitioners. The findings show that the gap between older and younger generations in their understanding of leadership is a major challenge, with the younger generation emphasizing leadership based on collaboration and competence, while the older generation associates leadership with authority and experience. Furthermore, disparities in access to education, economic opportunities, and digital literacy exacerbate the situation of youth leadership empowerment. The implications of this study highlight the importance of implementing transformational leadership that bridges generational differences, as well as the need for youth empowerment through inclusive education and relevant digital leadership training programs. This study offers recommendations for the development of more adaptive and equitable leadership training programs across all societal levels.